PRELIMINARY COMPARATIVE ANALYSIS OF THE HEALTH STATUS OF STUDENT ATHLETES OF SPORTS EDUCATIONAL INSTITUTIONS - Dilfuza Zaynitdinova Shuhrat qizi; Tursunov Nodirjon Botirovich (Web of Journals Publishing, 2025)
An initial comparative analysis of the state of health of athletes of students of Sports educational institutions is one of the important aspects of modern sports education. Sports students engage in a wide variety of sports in order to maintain and promote physical and mental health throughout their activities. Their state of health determines not only sports success, but also the overall quality of life. Therefore, the analysis of the state of health of students in sports educational institutions is important in increasing their physical activity and interest in sports.
Keywords: Sports, Health, Education, Competition, motivation, health, stress.